2019
DOI: 10.7759/cureus.6297
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Self-care Activities and Their Relation with Glycemic Control in Patients Presenting to The Indus Hospital, Karachi

Abstract: Open Access Original Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
2
11
1
2
Order By: Relevance
“…Patients who were supported by their families were protected from prolonged poor diabetes mellitus control in our study (OR = 0.65, 95% CI [0.45 -0.94]; p = 0.02). Similar results have been reported by some authors [15] [19]. This support from the family would help the patient to have a less contemptuous view of the disease.…”
Section: Adherence To Treatmentsupporting
confidence: 90%
See 2 more Smart Citations
“…Patients who were supported by their families were protected from prolonged poor diabetes mellitus control in our study (OR = 0.65, 95% CI [0.45 -0.94]; p = 0.02). Similar results have been reported by some authors [15] [19]. This support from the family would help the patient to have a less contemptuous view of the disease.…”
Section: Adherence To Treatmentsupporting
confidence: 90%
“…Studies in African research centers reported poor glycemic control of T2DM patients in proportions ranging from 68.3% to 83.3% [8]- [14]. These ranges were similar to those reported in Asia (81.6%) [15] but higher than those reported in Europe [16] (37.4%) and in the United States (38%) [17].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“… 10 , 11 , 13 , 17 , 35 Furthermore, high psychological distress was significantly associated with poor glycemic control, 10 , 25 , 37–39 and inadequate diabetes self-care behaviors. 9 , 40 …”
Section: Introductionmentioning
confidence: 99%
“…O diabetes melito (DM), caracterizado por quadro de hiperglicemia persistente, é uma das DCNT mais prevalentes 3,4 . As duas principais classificações da doença correspondem ao DM tipo 1, associado a fatores autoimunes, e o DM tipo 2, correlacionado com a resistência periférica à insulina e com a insuficiência gradual das células beta pancreáticas 5 .…”
Section: Introductionunclassified